DIFFERENTIAL EQUATIONS OF THE FOURTH ORDER WITH ORTHOGONAL POLYNOMIAL SOLUTIONS - Rojas Romero, Santiago César (2004)
In this paper we developed conditions for orthogonality of polynomial Solutions of the fourth order differential equations with polynomial coefficients. Also, we present the fourth order equations with Legendre polynomials, Laguerre polynomials and Hermite polynomials solutions.